Electromobility for all. Financial incentives for e-cycling. - Haubold, Holger (My University, 2016)
E-bikes offer numerous benefits: They allow for longer distances to be cycled, make it easier to overcome natural obstacles, make it possible to transport heavier goods and open up cycling for groups that have not cycled previously. For all of these reasons, electric bikes offer an enormous potential to replace car trips in Europe. ECF therefore recommends to adopt balanced policies and promotion strategies for electromobility that help to realise the potential of electrifying the transport system as a whole instead of only focusing on one mode. We suggest introducing subsidy schemes for e-bikes based on market conditions: (1) In markets with low sales figures, a purchase subsidy of 500 (around 10% of the current purchase subsidies of electric cars in many European countries) could help to bridge the price gap to conventional bikes and facilitate market uptake of electric bikes (including low-powered as well as speed pedelecs), which in its turn have a high potential to achieve modal shift from car trips to cycling. (2) In more mature markets, more targeted subsidy schemes e.g. for speed pedelecs and electric cargobikes due to their higher price or for charging infrastructure in small businesses can be an option. Subsidies for electric bikes could also be given as a reward for cancelling a car's registration. Besides these targeted purchase subsidies, which are at the centre of this report, other, more general, funding schemes for research and development or infrastructure like charging points and secure parking can also contribute to the promotion of electric cycling. In these areas, the EU could play a more active role in the promotion of electric cycling by including it in its e-mobility policies.
Keywords: Individualverkehr; Fahrradverkehr; Mobilität; Wirtschaft; Verkehrspolitik; Radverkehrspolitik; Elektromobilität; Finanzierung